2003
DOI: 10.3390/i4040158
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Karplus Relationship for NMR Spin-Spin Coupling Constants to Nonplanar Ring Systems: Pseudorotation of Tetrahydrofuran

Abstract: Karplus relationships for all 26 NMR spin-spin coupling constants (SSCCs) J of the pseudorotating tetrahydrofuran (THF) molecule were derived by expanding J as a function J(q,φ) of the puckering amplitude q and the pseudorotational phase angle φ. For this purpose, the conformational potential V(q,φ) of THF was determined at the MBPT(2)/ccpVTZ and B3LYP/6-31G(d,p) levels of theory. THF is a slightly hindered pseudorotor (MP2 barriers ∆E and ∆H are 0.1 -0.2 kcal/mol) with a puckering amplitude q = 0.396Å and a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 62 publications
4
34
0
Order By: Relevance
“…In addition to these three conformers, a couple of measurements 32,33 have also reported the possibility that C 1 is the ground-state symmetry of THF. However, most work 23,30,[34][35][36][37] does seem to support the notion that the nonplanar symmetrical C 2 point group symmetry is the global minimum (energy) conformer, with another local minimum conformer of the C s symmetry. In any event, Bouchiha et al 27 and Trevisan et al 25 noted that the structural bond-lengths and bond angles for three of the different configurations (C 2 , C s , and C 2v ) are very similar and so are their target properties.…”
Section: Spectroscopy Of Thf (C 4 H 8 O)mentioning
confidence: 99%
“…In addition to these three conformers, a couple of measurements 32,33 have also reported the possibility that C 1 is the ground-state symmetry of THF. However, most work 23,30,[34][35][36][37] does seem to support the notion that the nonplanar symmetrical C 2 point group symmetry is the global minimum (energy) conformer, with another local minimum conformer of the C s symmetry. In any event, Bouchiha et al 27 and Trevisan et al 25 noted that the structural bond-lengths and bond angles for three of the different configurations (C 2 , C s , and C 2v ) are very similar and so are their target properties.…”
Section: Spectroscopy Of Thf (C 4 H 8 O)mentioning
confidence: 99%
“…Melnik et al [21] carried out MP2/6-31+G(p,d) and B3LYP/6-31+G(p,d) calculations, which gave the twisted C 2 as a global minimum in perfect agreement with their experimental results. Wu and Cremer also reported, at the MP2/cc-pVTZ and B3LYP/6-31G(p, d) levels, the twisted 1 E geometry (C 2 ) to be the global minimum [16] lying ~0.2 kcal/mol below the C s geometry. Recently, Rayón and Sordo [24] performed a detailed theoretical study at the MP2/aug-cc-pVTZ including anharmonic ZPE correction and suggested that the envelopes C s are the global minima structures.…”
Section: Neutral Ground Statementioning
confidence: 99%
“…1, all of which appear to be connected along the pseudorotation path as a function of the pseudorotation angle f. A similar type of ring deformation is known to occur in the nucleosides and nucleotides and is closely related to higher order structure in the nucleic acids like DNA and RNA [17]. The preferred conformation of the isolated molecule in the gas phase is still debated, despite several experimental [18][19][20][21] and theoretical studies to clarify the situation [16,[21][22][23][24]. Recently, Yang at al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][18][19][20]) the bond lengths in five-membered rings depend markedly on the phase angle u. For the analysis of experimental data it is therefore reasonable to use a Fourier expansion of the geometrical parameters R(u) (e.g.…”
Section: Dependency Of Geometry On Pseudorotationmentioning
confidence: 99%